Effectiveness of Spectacle Correction for Children with Refractive Amblyopia in Surabaya - Audia Salwadiva; Sawitri Boengas; Jefman Efendi Marzuki (Vision Science and Eye Health Journal, 2026)
Introduction: Amblyopia is a condition characterized by decreased visual acuity in one or both eyes. This condition frequently occurs in children because at this stage, there is a critical period of visual development. Delayed treatment can lead to decreased or even permanent vision loss. Purpose: To determine the prevalence of refractive amblyopia in children and evaluate the effectiveness of spectacle correction on visual improvement in children aged 6-18 years diagnosed with refractive amblyopia. Methods: This was an observational analytic study with a retrospective cohort approach. The study included 29 subjects aged 6–18 years with refractive amblyopia. Visual acuity was assessed in subjects who met the inclusion criteria. Eyeglasses were prescribed and visual development was monitored. Best-corrected visual acuity (BCVA) was re-evaluated after one and six months of wearing glasses. Results: A total of 15,387 pediatric patients were screened, of whom 144 (0.94%) were diagnosed with refractive amblyopia. Twenty-nine subjects met the inclusion criteria. Significant improvements in visual acuity were observed at one month (P = 0.045) and six months (P = 0.002) after spectacle use. At one month, 37.5% of eyes improved by one line, while at six months, 31.8% showed similar improvement. The difference in effectiveness between one and six months was not statistically significant (P = 0.484). Conclusions: Spectacle correction alone is effective in improving visual acuity in children with refractive amblyopia.